ANALISIS RASIO AKTIVITAS SEBAGAI DASAR PENGUKURAN EFEKTIVITAS KINERJA KEUANGAN PT GARUDAFOOD PUTRA PUTRI JAYA TBK PADA PERIODE TAHUN 2023–2024 - Firman HP Munthe (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the financial performance of PT GarudaFood Putra Putri Jaya Tbk for the 2023–2024 period through an activity ratio approach. This analysis is conducted to assess the company’s level of efficiency in utilizing its operational assets to generate sales. The research employs a quantitative descriptive method by calculating several activity ratios, including inventory turnover, receivables turnover, working capital turnover, fixed asset turnover, and total asset turnover. The results indicate that all activity ratios increased in 2024 compared to 2023, reflecting improved efficiency in the management of inventory, receivables, working capital, as well as the utilization of fixed assets and total assets. These findings confirm that the company has been able to enhance its operational quality and improve the effectiveness of resource utilization. Overall, the financial performance based on activity ratios exhibits a positive trend, indicating that PT GarudaFood Putra Putri Jaya Tbk was in a healthy and competitive condition during the study period.